Targeting food security interventions when “everyone is poor”: The case of Ethiopia's Productive Safety Net Programme - Coll-Black, Sarah; Gilligan, Daniel O.; Hoddinott, John F.; Kumar, Neha; Taffesse, Alemayehu Seyoum; Wiseman, William (International Food Policy Research Institute, 2011)
In Ethiopia, as in many other African countries, there is a pressing need to improve household food security. An emerging consensus suggests that this is most easily accomplished through two development strategies with two complementary dimensions: investments that facilitate income generation and asset accumulation (infrastructure development, improved technologies for agriculture, etc.), and interventions that protect the poorest from hunger, prevent asset depletion and provide a platform on which the growth interventions can take place. Given limited resources for the latter, there needs to be an allocation mechanism. But in a country like Ethiopia, where poverty is widespread and income distribution relatively equal, how does targeting work? (Woldehanna et al. 2008); literally, when “everyone is poor".